A Randomized Controlled Clinical Trial Comparing Koshataki Ksharasutra with Apamarga Ksharasutra in Bhagandara (Fistula in Ano) Management - Kumar, Sunil; Senapati, B. C; Singh, Jitendra Kumar (Journal of Neonatal Surgery, 2025)
Bhagandara (Fistula in Ano) at modern parlance is a common anorectal condition prevalent in the populations worldwide and its prevalence is second highest after Arsha (hemorrhoids). Kshara Sutra(medicated thread) has been proved to be a big revolution in the treatment of fistula in ano. In the present clinical study, comparative study of Koshataki (Luffa acutangula) and Apamarga (Achyranthus aspera) Ksharasutra has been studied in the management of Bhagandara. Total 40 patients presenting with signs and symptoms of fistula-in-ano were registered of any age, sex etc. They were randomly divided into two groups - Group 'A': In this group total 20 patients of 'fistula in ano' were included and were treated by "Koshataki Ksharasutra". (Trial Group) Group 'B':- In this group total '20' patients of 'fistula in ano' were included and were treated by "Apamarga Ksharasutra". (Control Group) Assessment was done on objective parameters (Unit Cutting Time UCT, Induration, Tenderness) and subjective parameters (Pain, Itching, Discharge). After comparison of all above figures of signs & symptoms in group A and group B, we can conclude that the treatment used in Group A i.e. with Koshataki Ksharasutra is a good relief in treatment of Bhagandara